Instrumentos urbanos de captura da valorização imobiliária: uma análise conceitual - Corrêa, Marília Marton (2022)
The expansion and maintenance of the services offered by the government permeates fundamentally the way the federative entities self-finance. The cities, which achieved autonomy in the Federal Constitution of 1988, in particular, are, among the three spheres of the Federation, the most penalized: if on the one hand they are responsible for most of the services and investments necessary to guarantee their social functions, in accordance with article 182 of the active constitutional text, on the other hand they receive the smallest part of the total tax revenue. Two premises are important in this context. The first is to understand that public investment is also to maintain, with good quality, services already consolidated. And the second is that a city, to have good services, needs its citizens to contribute proportionally for that, based on a strong criterion of tax justice. To this end, there are several urban policy instruments capable of capturing the surplus resulting from real estate valuation, especially the one triggered by investments supported by all taxpayers. Such instruments, although provided for in the laws and present in important regulatory frameworks, such as the Master Plans, have not yet been effectively implemented in practice. Nevertheless, they are necessary elements to the idea of intelligent management in cities, because they support the growing demand for public investments capable of promoting social welfare. The objective of this work is to conduct a conceptual analysis on urban instruments for capturing real estate valuation based on international experiences, as well as the Brazilian policy of urban land value recapture, in Brazil.